Modification of NanoCrystalline Cellulose (NCC) by Hyperbranched Polymer - Zianor Azrina, Z. A.; Beg, M. D. H.; R. M., Yunus; Ridzuan, Ramli; A. K. M., Moshiul Alam (Informatics Publishing Limited, 2017)
Objectives: The surface modification of NanoCrystalline Cellulose (NCC) recently has been paid attention due to the increasing opportunities in the application. The objective of this paper is to modify the surface of NCC by the HyperBranched Polymer (HBP) with hydroxyl terminal groups ends. Methods/Statistical Analysis: The NCC surfaces were modified with HBP using solvent evaporation methods. First, the NCC was synthesized via ultrasound assisted acid hydrolysis process and the obtained NCC was surface coated by using HBP with different concentration through solvent evaporation technique. Finally, the obtained NCC and Modified NCC were characterized by using FTIR, XRD and TGA. Findings: Results revealed that there are significant differences of FTIR pattern analysis indicated that the NCC has been modified, however the modification NCC with HBP under various conditions did not change the X-ray patterns of NCC which indicates that the HBP only coated on the surface of NCC. Application/Improvements: This modification of NCC showed promising results which can be used for various applications.